2018
DOI: 10.1021/acs.macromol.8b01027
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intrachain Cross-Linking on the Thermomechanical Behavior of Bulk Polymers Assembled Solely from Single Chain Polymer Nanoparticles

Abstract: Chemical cross-linking of polymer chains is a powerful means for tailoring the thermomechanical properties of bulk plastics. Nonetheless, upon cross-linking, processability is reduced as the plastic becomes thermoset. Here, molecular dynamics simulations are used to study the effects of intramolecular chemical cross-linking on chain topology and thermomechanical properties of a bulk, thermoplastic polymer. Polyethylene (PE)-like plastics are assembled purely from chains which have undergone a set level of intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 43 publications
(67 reference statements)
3
20
1
Order By: Relevance
“…The glass transition temperature was measured using differential scanning calorimetry (DSC) and dynamic mechanical thermal analysis (DMTA) to provide some experimental indications on the effect of intramolecular CL on segmental dynamics. In agreement with ours and others previous results, T g increases in PBMA with increasing CL degree (Table ). T g 's determined by MD simulations found the same trend ( Table 2 ).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The glass transition temperature was measured using differential scanning calorimetry (DSC) and dynamic mechanical thermal analysis (DMTA) to provide some experimental indications on the effect of intramolecular CL on segmental dynamics. In agreement with ours and others previous results, T g increases in PBMA with increasing CL degree (Table ). T g 's determined by MD simulations found the same trend ( Table 2 ).…”
Section: Resultssupporting
confidence: 93%
“…For EL, E1 and E2, pronounced plastic deformation accompanied by strain hardening is seen, but decreases with CL degree. Interestingly, this influence of intramolecular CL on PBMA SCPNs was predicted by our previous MD study and was again observed in the current MD study (Figure c) . By addition of intramolecular CLs, all segments are brought closer together, increasing the intramolecular interactions (Figures S30 and 31, SI) and producing more rigid SCPNs, resulting in a stiffer material.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…In addition, it has been shown that mechanochemistry concentrates in short CLs in thermoset systems, presumably due to their restricted mobility . Our results can be similarly rationalized—shorter intramolecular CLs induce slower segmental dynamics (as seen by the increase in Tg) and more rigid conformation, therefore being more susceptible to mechanical stress compared to CLs made from longer chains, which can “absorb” the strain through unfolding.…”
Section: Resultssupporting
confidence: 68%